Inverse relationship between erythrocyte size and platelet reactivity in elderly. (17th February 2017) - Milovanovic, M.; Nilsson, S.; Winblad, B.; Jelic, V.; Behbahani, H.; Shahnaz, T.; Oweling, M.; Järemo, P.
Abstract: Previous work indicates that erythrocytes (RBCs) accumulate β-amyloid X-40 (Aβ40 ) in individuals with Alzheimer disease (AD) and to a lesser extent in healthy elderly. The toxin damages RBCs and increases their mean corpuscular volume (MCV). Furthermore, AD platelets demonstrate lower reactivity. This study investigated interactions between RBCs and platelets. Older individuals with moderate hypertension ( n = 57) were classified into two groups, depending on MCV in whole blood: The MCV high group comprised individuals with higher MCV ( n = 27; 97 ± 3(SD) fl) and MCV low group had relatively lower MCV ( n = 30; 90 ± 3(SD) fl). Flow cytometry was used to determine platelet reactivity, i.e., the surface binding of fibrinogen after provocation. Adenosine diphosphate (ADP) and a thrombin receptor-activating protein (TRAP-6) were used as agonists. Subsequently, blood cells were divided according to density into 17 subfractions. Intra-RBC Aβ40 content was analyzed and in all platelet populations surface-bound fibrinogen was determined to estimate platelet in vivo activity. We found Aβ40 inside RBCs of approximately 50% of participants, but the toxin did not affect MCV and platelet reactivity. In contrast, MCV associated inversely with platelet reactivity as judged from surface-attached fibrinogen after ADP (1.7 μmol/L) ( p < 0.05) and TRAP-6 provocation (57 μmol/L ( p = 0.01) and 74 μmol/L ( p < 0.05)). In several density fractions ( nos . 3, 4, 8, 11–13 ( p < 0.05) and nos . 5–7 ( p < 0.01)) MCV linked inversely with platelet-attached fibrinogen. In our community-dwelling sample, enhanced MCV associated with decreased platelet reactivity and lower in vivo platelet activity. It resembles RBCs and platelet behavior in AD-type dementia.